Design and Characterization of Evanescently Coupled Uni-Traveling Carrier Photodiodes with a Multimode Diluted Waveguide Structure - 张云霄 潘教清 赵玲娟 朱洪亮 王圩 (Chinese physics letters, 2010)
A new evanescently coupled uni-traveling carrier photodiode （EC-UTC-PD） is designed, fabricated and characterized, which incorporates a multimode diluted waveguide structure and UTC active waveguide structure together. A high responsivity of 0.68 A/W at 1.55-μm without an anti-reflection coating, a linear photocurrent responsivity of more than 21 mA, and a large -1 dB vertical alignment tolerance of 2.5 μm are achieved.